How students leverage assignment submission flexibility — A case study - Sean Conner (Heliyon)
Recent pedagogical trends in post-secondary education focus on how providing students with greater autonomy through assignment submission flexibility offers benefits ranging from increased learning to stress reduction. Unfortunately, the relationship between submission flexibility and any specific benefit is not firmly established. One explanation for this is a potential misalignment between anticipated benefits and an understanding of how most students leverage extended opportunities for assignment completion. The goal of this study was to investigate the relationship between assignment submission flexibility and how students used the opportunity. Quantitative evidence reveals that most students routinely maximized the time taken before submitting assignments. This occurred independent of assignment type, teaching modality, or the duration of assignment availability. The results support a conclusion that most students do not capitalize on increased flexibility to meet the demands of their unique schedules. Instead, they appear to adapt their schedules to submit assignments shortly before a perceived deadline.